2011
DOI: 10.1093/hmg/ddr366
|View full text |Cite
|
Sign up to set email alerts
|

Functional and physical interaction between the mismatch repair and FA-BRCA pathways

Abstract: Fanconi anemia (FA) is a rare genetic disorder characterized by bone marrow failure and an increased risk for leukemia and cancer. Fifteen proteins thought to function in the repair of DNA interstrand crosslinks (ICLs) comprise what is known as the FA-BRCA pathway. Activation of this pathway leads to the monoubiquitylation and chromatin localization of FANCD2 and FANCI. It has previously been shown that FANCJ interacts with the mismatch repair (MMR) complex MutLα. Here we show that FANCD2 interacts with the MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 68 publications
1
46
0
1
Order By: Relevance
“…34 The pivotal FA protein FANCD2 was subsequently shown to interact with MSH2 and MLH1. 35 Our report indicates that the presence of biallelic BRCA2 mutations should be considered in families with early-onset breast and CRCs, even in the absence of cardinal features of FA.…”
Section: Early-onset Crcs and Biallelicmentioning
confidence: 64%
“…34 The pivotal FA protein FANCD2 was subsequently shown to interact with MSH2 and MLH1. 35 Our report indicates that the presence of biallelic BRCA2 mutations should be considered in families with early-onset breast and CRCs, even in the absence of cardinal features of FA.…”
Section: Early-onset Crcs and Biallelicmentioning
confidence: 64%
“…Although the type of DNA lesion preferentially targeted by each mechanism is known, 183 notably, there is evidence for direct interaction between components of the different repair systems as well as between DNA repair and the p53 pathway. [186][187][188][189][190][191][192][193][194] Although loss of apoptotic/senescent function in theory should be expected to cause therapy resistance, the opposite may be the case in DNA repair. Drugs like alkylating agents generate 8-oxoguanine and single-strand breaks subject to repair by BER, whereas platinum-containing compounds generate interstrand crosslinks and double-strand breaks.…”
Section: Dna Repair Pathwaysmentioning
confidence: 99%
“…Another important non-BRCA1/BRCA2 (55). FA is a rare autosomal or X-linked recessive genetic heterogeneous disorder characterized by spontaneous chromosomal breaks, abnormal DNA repair and clinical problems including congenital abnormalities, endocrinopathies, early onset bone marrow failure and an increased susceptibility to cancer and leukemia (36). Similar to BRCA, the FA proteins form a functional core complex and are associated with a novel pathway required for DNA damage repair, particularly DNA interstrand cross-links.…”
Section: Lynch Syndromementioning
confidence: 99%
“…1, BRCA1 forms a multi-subunit protein complex, which includes DNA damage repair proteins, including FA and MMR proteins. Recent studies showed a functional interaction between FANCJ and the MMR complex MutL α, which is essential for establishment of DNA interstrand cross-links (36). FANCD2 is required for binding between MSH2 and MLH1, which are involved in the monoubiquitination of FANCD2, leading to recruitment of ATR and then activation of CHK1 and TP53.…”
Section: Lynch Syndromementioning
confidence: 99%